106 Agriculture Residues as a Possible Sustainable Approach to Replacing Antibiotics in Animal Nutrition. (7th May 2021) - Ekmay, Ricardo
Abstract: The last several years has seen a substantial increase in the investment and development of alternative proteins to lower the environmental footprint of animal agriculture. In addition to insects, single cell proteins (SCP), i.e. algae, bacteria, yeast, have received renewed attention due to their ability to utilize unconventional carbon feedstocks. Traditionally, conventional sugar streams such as corn syrup or molasses have been used for cultivation of SCP. However, algal and bacterial meals are looked at as potential solutions for industrial carbon waste such as carbon dioxide and methane. Yeasts have the ability to use pentose sugars that are found in lignocellulosic materials, i.e. agricultural and forestry residues. Much of the discourse surrounding these alternative protein sources has been on the environmental impact of their production, but less so on the impact of their use. In particular, the impact of single cell proteins on nutrient utilization and gastrointestinal health warrants attention. Nutritional value remains varied among SCP products and dependent on microbial strain and down-stream processes. Maintaining high protein digestibility, and reducing fermentable protein, as well as maintaining high phosphorus digestibility remains a critical nutritional and environmental strategy. Recent findings have indicated that the microbial strain and the carbon feedstock on which it is grown on may have an interactive effect on gastrointestinal health. In particular, yeast products can be characterized as generally anti-inflammatory, but cultivation on lignocellulosic residues appears to enhance these properties. Bacterial meals are known to contain pro-inflammatory components such as lipopolysaccharides and peptidoglycans, however, in some instances, they may also produce bioactive molecules that result in a net positive impact. It remains critical to evaluate alternative proteins in the context of whole animal health and consider the environmental impact of their use as well as their production.